Analysis of the methodologies created for libraries in the construction of authority control - Menocal, Anamarys Toscano; Rodríguez, María del Rosario Fernández (Advanced Notes in Information Science, 2024)
Libraries are immersed in a process of structural change, where the implementation of new competency practices means bringing them into conformity with the needs and demands that arise in the information and knowledge society. The growth of technologies and information sources, which are scattered on the Internet, implies the task of obtaining information from a large number of sources available on the Web. The realization of information queries from heterogeneous and geographically dispersed sources requires the implementation of methodologies and regulations, as well as the construction of tools. The research aims to analyze the methodologies created so far in libraries, for the realization of authority control. It was necessary to use both theoretical and empirical methods in the collection of information. In the last 10 years, it is evident in the analyzed methodologies, the beginning of the use of Resource Description Framework (RDF) format for linking and interoperability of data. What used to be a long and time-consuming process, with the use of RDF, the speed and flexibility of the information expressed in this format can be verified.